Fusion gene profile of biphenotypic sinonasal sarcoma: an analysis of 44 cases. Issue 6 (23rd September 2016) - Fritchie, Karen J; Jin, Long; Wang, Xiaoke; Graham, Rondell P; Torbenson, Michael S; Lewis, Jean E; Rivera, Michael; Garcia, Joaquin J; Schembri‐Wismayer, David J; Westendorf, Jennifer J; Chou, Margaret M; Dong, Jie; et al.
Abstract : Aims: Biphenotypic sinonasal sarcoma (SNS) is a locally aggressive tumour that occurs in the sinonasal region. PAX3 – MAML3 has recently been identified as a recurrent fusion gene event in this entity; however, a subset of tumours harbour alternative PAX3 rearrangement without the involvement of MAML3 . In this study we sought to characterize the molecular profile of a large series of cases, with a special emphasis on tumours with alternative fusions. Methods and results: Forty‐four examples of SNS were screened by fluorescence in‐situ hybridization and reverse transcription polymerase chain reaction to better characterize its molecular profile and identify potential novel fusion genes. Twenty‐four were positive for PAX3–MAML3 (55%), 15 showed rearrangements of PAX3 without MAML3 involvement (34%), one showed rearrangement of MAML3 without PAX3 involvement, and four were negative for the involvement of either gene (9%). Among 15 cases with PAX3 involvement only, three were found to harbour PAX3–FOXO1 . Two of these cases arose in the nasal cavities of female patients (aged 31 and 47 years), and one showed bilateral involvement of the nasal cavities of a 35‐year‐old male. A fourth case involved the skull base of a 47‐year‐old male, and was positive for PAX3–NCOA1 . Patients with fusion‐negative tumours were slightly older. Conclusion: More than half of the SNSs in this series were positive for PAX3–MAML3 . However, a subset of tumours may harbour alternative PAX3 fusion genes or show no involvement of PAX3 . Except for a possible weak association between age and molecular profile, the overall morphological and immunophenotypic features of all cases seem to be similar. Because of the rarity of these tumours, the impact of the molecular profile on the clinical course of these tumours remains to be determined.